اثر استراتيجية الخريطة الذهنية في اكتساب المفاهيم الجغرافية لدى طالبات الصف الخامس الادبي في مادة الجغرافية (Journal Of Educational and Psychological Researches, 2015)
The present study aimed to impact Strategy mental map in the acquisition of geographical concepts at the fifth-grade students in the literary geography classes. To achieve the objectives of the research formulated researcher null hypothesis (no statistically significant difference at the level (0.05) between the average scores of students who Adersna using a mind map, and who Adersna using the method usual in the acquisition of concepts geographic fifth grade literary). Has chosen researcher design Altjeribeachtar researcher Design The partial adjustment for both experimental and control groups Pachtearlakedzab concepts. The sample Seateetmthel graders secondary schools under the Directorate General of Educational Baghdad Rusafa II has chosen the researcher randomly school and chose researcher Division (a) were randomly assigned to be the experimental group and the Division (c) to be the control group reached the total of the two groups (67 students). And by (34) and (33) a control group. school supplies formulated educational objectives relating to the acquisition of concepts. Preparation and scientific material. And prepare lesson plans for both groups. Then a promising researcher achievement test Uday corrupted from (50), paragraph-risk trial of type objective tests, The research results showed has developed recommendations and proposals.